EFFECTS OF AVURVEDIC SHODHANA (PROCESSING) ON DRIED TUBEROUS ACONITE (Aconitum napellus Linn.) ROOT - Arindam Paul; Umang Gajjar; Jignasa Donga (Indonesian Journal of Pharmacy, 2013)
Aconite (Aconitum napellus Linn.) commonly known as atis is a poisonous plant used extensively as antihypertensive, antipyretic, analgesic and antirheumatic. Ayurveda recommended the administration of aconite roots only after purification, i.e., boiling roots in cow’s urine (Gomutra). In the present study an attempt was made to compare the pro-arrhythmic and antihypertensive effects of powdered aconite root purified by shodhana process with that of unpurified form of aconite roots in order to provide scientific support of the claim in ayurvedic texts that purification of aconite root by shodhana process retains its antihypertensive activity and is devoid of pro-arrhythmic activity. Aconite root treatment in both forms purified and unpurified) caused significant reduction in BP when compared with diseased control group (P<0.05). The unpurified aconite root group showed significant increase in heart rate, increase in QRS complex time and increase in QT interval, however these parameters were statistically insignificant in purified aconite root treated group. The PRA, SC and BUN levels was significantly decreased in aconite root treatment groups. The probable mechanism of antihypertensive activity of aconite root can be attributed to decrease in plasma renin activity, decrease in oxidative stress and increase in NO levels. Key words: Aconite, shodhana process, antihypertensive, proarrhythmic